Implementasi Konseling Traumatik Di Lingkungan Sekolah SD Negeri 124 Binanga Pasca Bencana Banjir Di Kecamatan Hutabargot Kabupaten Mandailing Natal - Husni Ismail; Anni Marhamah; Abd. Aziz (Journal of Innovative and Creativity, 2025)
Flood disasters that occurred in Hutabargot District, Mandailing Natal Regency, caused not only physical damage but also significant psychological impacts on elementary school students. Children, as a vulnerable group, experienced difficulties in psychological adjustment (al-takayyuf al-nafsī), excessive fear (al-khawf al-mufriṭ), decreased concentration, and declining learning motivation in the post-disaster period. This article aims to examine and describe the implementation of traumatic counseling (al-irsyād al-nafsī al-‘ilājī ba‘da al-ṣadmah) at SD Negeri 124 Binanga as an effort to support students’ psychosocial recovery after the flood. This study employed a qualitative descriptive approach. The research subjects were students affected by psychological trauma, while supporting informants included classroom teachers, psychosocial counseling teachers, the school principal, and parents. Data were collected through observation, semi-structured interviews, and documentation, and analyzed using the Miles and Huberman model, which consists of data reduction, data display, and conclusion drawing. The findings indicate that traumatic counseling implemented through individual and group counseling, play therapy (al-‘ilāj bi al-la‘ib), expressive activities, and the integration of religious values such as patience (al-ṣabr) and trust in God (al-tawakkul) had a positive impact on students’ psychological recovery. Students showed reduced anxiety, improved social interaction, and increased concentration and learning motivation. Therefore, traumatic counseling in the school setting plays an effective curative and preventive role in strengthening children’s psychological resilience (al-munā‘ah al-nafsiyyah) following natural disasters.